TOWARDS THE STRENGTHENING OF THE TEACHING ROLE FROM ITS PROFESSIONALIZATION - Fernandez , Diana; Nataly, Garcia (Top Educational Review Journal (TERJ), 2023)
This paper focuses on analyzing the relationship between pedagogical content knowledge (PCK) and teaching professionalization, taking into account a case study by a Social Science teacher. The case study was conducted in an official school with sixth graders. The intervention focused on promoting in the teacher the design of teaching strategies taking into account the elements of the PCK. Given this, the teacher designed ICT-mediated teaching strategies, with different technological tools; which she integrates consistently and according to teaching needs, bearing in mind not only the curriculum but also the pedagogical intentionality. Thanks to that, it was possible to understand when assessing the impact of the intervention, that her level of teaching professionalization was strengthened, since the teacher was evoked to plan her teaching tools based on the aspects that make up the PCK, refining her disciplinary knowledge, technological competences and also the importance of the emotional aspect in the teacher professionalization since positive emotions fostered on her, the ability to reflect on their pedagogical practices. Given the above, it is important to highlight the teaching professionalization in the educational processes